Does deacclimation reverse the changes in structural/physicochemical properties of the chloroplast membranes that are induced by cold acclimation in oilseed rape? - Rys, Magdalena (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 The Authors. Published by Elsevier Masson SAS.. All rights reserved.